Odpowiedzi

2010-03-04T22:26:06+01:00
A) -(2x-1)=4
-2x+1 = 4 /-1
-2x = 3 /:(-2)
x = - 1,5

b) 2(x+1)=x
2x+2 = x /-2
2x = -2 /:2
x = -1

c) 2t-(3t+1)=6
2t-3t-1 = 6
-t-1 = 6 /+1
-t = 7 /*(-1)
t = -7

d) -(4+x)=2(3-x)
-4-x = 6-2x /+x -6
-x = -10 /*(-1)
x = 10

e) 3(y+6)-y=2(y+9)
3y+18-y = 2y+18
2y+18 = 2y+18
równanie tożsame
L=P

f) (x-7)-2(3x+5)=3
x-7-6x-10 = 3
-5x-17 = 3 /+17
-5x = 20 /:(-5)
x = -4
2010-03-04T22:27:44+01:00
A) -(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3|:-2
x= -3/2 = -1i1/3

b) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2

c) 2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7|:-1
t=-7

d) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

e) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0

f) (x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=3+10+7
-5x=20|:-5
x= -4
2010-03-04T22:35:28+01:00
A) -(2x-1)=4
-2x+1 = 4 /-1
-2x = 3 /:(-2)
x = - 1,5

b) 2(x+1)=x
2x+2 = x /-2
2x = -2 /:2
x = -1

c) 2t-(3t+1)=6
2t-3t-1 = 6
-t-1 = 6 /+1
-t = 7 /*(-1)
t = -7

d) -(4+x)=2(3-x)
-4-x = 6-2x /+x -6
-x = -10 /*(-1)
x = 10

e) 3(y+6)-y=2(y+9)
3y+18-y = 2y+18
2y+18 = 2y+18
równanie tożsame
L=P

f) (x-7)-2(3x+5)=3
x-7-6x-10 = 3
-5x-17 = 3 /+17
-5x = 20 /:(-5)
x = -4